2013
DOI: 10.18388/abp.2013_2031
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of heavy metals (Mn, Co, Ni, Cr, Ag, Pb) in coffee.

Abstract: Aim: Technologies involved in roasting coffee beans, as well as the methods used to prepare infusions, vary according to culture, and contribute to differences in the concentration of elements in the drink. Materials and Methods: Concentrations of six elements: manganese (Mn), cobalt (Co), nickel (Ni), chrome (Cr), silver (Ag) and lead (Pb) were investigated in coffee infusions from eleven samples of coffee, roasted and purchased in four countries: Bosnia and Herzegovina, Brazil, Lebanon and Poland. Metal conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 20 publications
(16 reference statements)
0
21
1
Order By: Relevance
“…The ranges of estimated intake of investigated metals per capita/year, based on coffee consumption obtained from (21) were: Na: 80.6– 225.1; K: 125860¬–204184.6; Ca: 4650–5821.8; Mg: 11160– 13187.4; Fe: 218.2–304.4; Cu 40.3–102.3; Zn:30.8–38.3; Al: 10.8–37.3; Ni: 4.3–7.2; Pb: 0.07–0.13; Cd: 0.07–1.14 mg/ per capita/year, and none of the metals tested exceeded the level that could pose a health risk. Our previous study of coffee purchased in Bosnia has shown similar values for Ni intake 3.83–5.68, but higher values for Pb 4.76–7.56 mg/ per capita/year (36). Unfortunately, in the previous study, we did not investigate green coffee beans.…”
Section: Discussionmentioning
confidence: 81%
“…The ranges of estimated intake of investigated metals per capita/year, based on coffee consumption obtained from (21) were: Na: 80.6– 225.1; K: 125860¬–204184.6; Ca: 4650–5821.8; Mg: 11160– 13187.4; Fe: 218.2–304.4; Cu 40.3–102.3; Zn:30.8–38.3; Al: 10.8–37.3; Ni: 4.3–7.2; Pb: 0.07–0.13; Cd: 0.07–1.14 mg/ per capita/year, and none of the metals tested exceeded the level that could pose a health risk. Our previous study of coffee purchased in Bosnia has shown similar values for Ni intake 3.83–5.68, but higher values for Pb 4.76–7.56 mg/ per capita/year (36). Unfortunately, in the previous study, we did not investigate green coffee beans.…”
Section: Discussionmentioning
confidence: 81%
“…Finally, a number of other studies ( n = 45) were identified by the literature search that highlighted coffee as a potential source of certain unwanted/toxic constituents, such as ochratoxin A (StuderRohr and others , ), furan (Crews and others ; Altaki and others ), heavy metals (Taylor and others ; Nedzarek and others ) and acrylamide (Bjellaas and others ; Eerola and others ). For the most part, however, such studies did report that measured/estimated intake levels were well below estimated daily acceptable intakes or that coffee was not a major source, therefore deemed safe (Perez de Obanos and others ; Akdemir and others ; Guenther and others ; Ates and others ; Coronel and others ).…”
Section: Resultsmentioning
confidence: 99%
“…Metals disturb ionic balance and mineral regulation, induce oxidative damage to cell structures, produce injury to DNA and induce cancer transformations. 128 Nędzarek et al 129 studied Mn, Co, Ni, Cr, and Ag levels in coffee. Such levels were shown to be too low to influence human health.…”
Section: Safety Concerns Of the Use Coffee By-products As A Natural Smentioning
confidence: 99%